Saving Private Ryan [videorecording (Blu-Ray)] - Spielberg, Steven, 1946-; Bryce, Ian; Gordon, Mark, 1956-; Levinsohn, Gary; Rodat, Robert; Hanks, Tom; Burns, Edward, 1968-; Damon, Matt; Sizemore, Tom, 1961-; Williams, John, 1932- (Sapphire series., 2010)
A squad of American soldiers moves beyond the beach of the Normandy D-Day invasion. The men, then, embark on a dangerous special mission with Captain John Miller in charge. Miller must take his men behind enemy lines to find Private James Ryan, whose three brothers have been killed in combat. Faced with impossible odds, the men question their orders. Surrounded by the brutal reality of war, each man searches for his own answer.